2011
DOI: 10.1007/s00109-011-0804-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle

Abstract: Right ventricular hypertrophy (RVH) and RV failure are major determinants of prognosis in pulmonary hypertension and congenital heart disease. In RVH, there is a metabolic shift from glucose oxidation (GO) to glycolysis. Directly increasing GO improves RV function, demonstrating the susceptibility of RVH to metabolic intervention. However, the effects of RVH on fatty acid oxidation (FAO), the main energy source in adult myocardium, are unknown. We hypothesized that partial inhibitors of FAO (pFOXi) would indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
188
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 29 publications
11
188
0
Order By: Relevance
“…Recent human and animal studies show evidence that there is a glycolytic shift in PAH and that these alterations are associated with an activation of glycolytic genes such as GLUT1, PDH and PDK (Oikawa et al, 2005;Fang et al 2012;Archer et al 2013) Our findings support this premise as demonstrated by elevated FDG SUVs in the RV and associated upregulation in glucose transporter GLUT4. There was a strong inverse correlation between increased FDG uptake and RV function suggesting that the glycolytic shift is maladaptive.…”
Section: Cardiac Changes In Metabolismsupporting
confidence: 83%
See 4 more Smart Citations
“…Recent human and animal studies show evidence that there is a glycolytic shift in PAH and that these alterations are associated with an activation of glycolytic genes such as GLUT1, PDH and PDK (Oikawa et al, 2005;Fang et al 2012;Archer et al 2013) Our findings support this premise as demonstrated by elevated FDG SUVs in the RV and associated upregulation in glucose transporter GLUT4. There was a strong inverse correlation between increased FDG uptake and RV function suggesting that the glycolytic shift is maladaptive.…”
Section: Cardiac Changes In Metabolismsupporting
confidence: 83%
“…During episodes of ischemia, there is an activation of AMPK and subsequently an increase in FAO. Although overall myocardial oxidative metabolism is reduced, FAs dominate as the main substrate source for residual oxidative phosphorylation (Fang et al, 2012). Myocardial FA metabolism is accelerated (Obrzut et al, 2010) as a compensatory mechanism to generate more fuel and inhibit apoptosis when exposed to ischemic stress however, sustained accelerated FAO rates inhibit glucose oxidation and reduce cardiac efficiency (Dyck et al, 2006).…”
Section: Regulating Faomentioning
confidence: 99%
See 3 more Smart Citations